PENGARUH RETURN ON ASSET, FIRM SIZE DAN PRICE EARNING RATIO TERHADAP RETURN SAHAM: PENGARUH RETURN ON ASSET, FIRM SIZE DAN PRICE EARNING RATIO TERHADAP RETURN SAHAM - Aldina Khoirul Fitroh; Fitri Ella Fauziah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
The purpose of this study was to determine the effect of return on asset, firm size, and price earning ratio on stock return. The objects chosen in this study were mining sector companies listed on the Indonesia Stock Exchange from 2015 to 2019. This research is a descriptive study with a quantitative approach. The number of samples used was 38 companies taken through purposive sampling. This study uses secondary data. The data analysis method used is Descriptive Statistics, Classical Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis. The results showed that return on asset variable (X1) had a significant positive effect on stock return with a significance value of 0.000, firm size variable (X2) had no effect on stock return with a significance value of 0.164, and for price earning ratio variable (X3) shows that there is no effect on stock return with a significance value of 0.000, and for the audit tenure variable (X4) significant positive effect on the integrity of financial statements.